(untitled) (Research, Society and Development, 2022)
Quality of life is an eminently human notion and encompasses many meanings that reflect knowledge, experiences and values of individuals and communities. care provided. This article aimed to: evaluate the quality of life of nurses working in general emergency. To work on the object in question, a cross-sectional field study with a quantitative approach was used. It was carried out in an emergency hospital in Recife-PE. The study complied with the determinations of the Declaration of Helsinki and Resolution 196/96 of the National Commission for Ethics and Research in Human Beings and was only started after approval by the Ethics Committee. The population surveyed consisted of 33 general emergency nurses from the target emergency hospital, from June to July 2009. The instrument used to determine quality of life was the SF-36. The general average of quality of life was 62%, the highest average was 90% and the lowest 20%, the highest domain was functional capacity with 76% and the lowest was vitality with 53%. The best measure of quality of life is not how much a service is offered, but how close the results are to the fundamental goals of prolonging life, relieving pain, restoring joint and preventing disability, seeking to reduce the impact of disease on the individual’s life.